De macht van de dood en de kracht van God: Enkele Bijbelse perspectieven - Weren, Wilhelmus Johannes Cornelis (HTS teologiese studies, 2012)
The might of death and the power of God: Some biblical perspectives. This article investigates how the might of death and the power of God are related in biblical writings. Factually, there are various biblical images concerning this relationship. Four of them are discussed in this contribution. Firstly, according to many texts, there is no afterlife and God’s power is limited and he is not able to save people after they have died. Secondly, view is disputed in other texts in which it is emphasised that the life of people who are faithful to God and his Torah, will have an open ending. This hope is based on God’s power and not on an indestructible personal core or some divine dimension deep within human beings. Thirdly, the most well known idea is the concept of resurrection which originated in Judaism and emerged when in the second century BCE martyrs died because of their religious convictions. Fourthly, this model has been applied to Jesus, who after having been rescued from death by God, was placed in a position that in many respects is similar to God’s position. In this article recent discoveries about developments in biblical ideas about God’s and Jesus’ competence and functions are integrated.